2006
DOI: 10.1021/bi060452+
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Pore Formation by Type III Toxin Translocators ofPseudomonas aeruginosa

Abstract: Type III secretion/translocation systems are essential actors in the pathogenicity of Gram-negative bacteria. The injection of bacterial toxins across the host cell plasma membranes is presumably accomplished by a proteinaceous structure, the translocon. In vitro, Pseudomonas aeruginosa translocators PopB and PopD form ringlike structures observed by electron microscopy. We demonstrate here that PopB and PopD are functionally active and sufficient to form pores in lipid vesicles. Furthermore, the two transloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 42 publications
8
84
2
Order By: Relevance
“…In addition, this observation also supports in vitro studies performed on other translocon molecules of Salmonella (40), Yersinia (41,43), and Shigella (42). These results suggest that, in Pseudomonas, PopB could be the major translocon component that binds most stably to target membranes upon infection, whereas PopD remains superficially associated to the bilayer, a suggestion that is in agreement with model membrane studies which showed that PopB plays the central role in pore formation (44,45).…”
Section: Resultssupporting
confidence: 87%
“…In addition, this observation also supports in vitro studies performed on other translocon molecules of Salmonella (40), Yersinia (41,43), and Shigella (42). These results suggest that, in Pseudomonas, PopB could be the major translocon component that binds most stably to target membranes upon infection, whereas PopD remains superficially associated to the bilayer, a suggestion that is in agreement with model membrane studies which showed that PopB plays the central role in pore formation (44,45).…”
Section: Resultssupporting
confidence: 87%
“…LUV Leakage Assay-LUV were prepared with 5 mM phosphate-citrate, pH 7, containing 50 mM sulforhodamine B (SRB) (Molecular Probes) as previously described (27). After filtration, unincorporated dye was removed by size exclusion chromatography on a PD10 column (Amersham Biosciences) equilibrated with 5 mM phosphate-citrate, 50 mM or 200 mM NaCl, pH 7.…”
Section: Methodsmentioning
confidence: 99%
“…Buffer only, buffer containing the appropriate detergents, IpgC, or IpaB/IpgC were used as negative controls for liposome disruption, as appropriate. Release of 3, 10, 40, and 70 kDa fluorescein-labeled dextrans from lipid vesicles was monitored using a modified protocol described previously 37 following the addition of 15 nM oligomeric IpaB. It is important to note that all of these release assays are strongly dependent on protein and liposome concentration 25 as well as the final concentration of detergent.…”
Section: Preparation Of Phospholipid Vesiclesmentioning
confidence: 99%